A COMPARATIVE ANALYSIS OF PAP SMEAR AND COLPOSCOPIC FINDINGS IN INDIVIDUALS PRESENTING WITH VAGINAL DISCHARGE AT A TERTIARY CARE OUTPATIENT DEPARTMENT: A CROSS-SECTIONAL STUDY. - Kumari, Punita; Khetan, Rajeev Kumar; Pratima (Student's Journal of Health Research Africa, 2025)
Background Cervical cancer is a predominant cause of cancer-related mortality in women globally. Screening techniques, such as Pap smear and colposcopy, are essential for detecting precancerous lesions, facilitating prompt intervention, and alleviating the disease burden. Methods This cross-sectional study was conducted in the Obstetrics and Gynaecology Department, Sri Krishna Medical College and Hospital, Muzaffarpur, Bihar, over one year. A total of 250 women aged 35–55 years underwent Pap smear, colposcopy, and biopsy for cervical lesion assessment. Results Among the participants, 34.0% had high-grade squamous intraepithelial lesions (HSIL), 22.4% had low-grade squamous intraepithelial lesions (LSIL), and 21.2% showed inflammatory changes on Pap smear. Colposcopy revealed CIN I in 48.0% of cases, CIN II–III in 36.4%, and CIN III in 15.6%. Histopathological confirmation showed 83.2% had precancerous lesions, with 7.2% diagnosed with squamous cell carcinoma and 1.2% with adenocarcinoma. Among the total study population (n = 250), 83.2% (208 patients) had abnormal findings suggestive of precancerous or cancerous cervical lesions, while 16.8% (42 patients) showed normal or non-precancerous findings. This corresponds to a prevalence of abnormal cervical pathology of 83.2% in the present study cohort. The study demonstrated that combining Pap smear screening with colposcopic evaluation and targeted biopsy significantly improved early detection of precancerous cervical lesions. This integrated diagnostic approach enabled timely intervention, reducing the risk of progression to invasive cancer. Conclusion The study highlights the high prevalence of precancerous cervical lesions, emphasizing the necessity of early screening. Colposcopy demonstrated higher diagnostic accuracy than Pap smear, reinforcing its role in early cervical cancer detection.